THEORETICAL AND METHODOLOGICAL FUNDAMENTALS OF CLUSTERING AS A TOOL FOR MANAGING THE INNOVATION AND INVESTMENT DEVELOPMENT OF INDUSTRIAL ENTERPRISES - Voinycha , Л.; Kozhel , П. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The research discusses the theoretical aspects and methodological approaches to clustering in the context of managing the development of industrial enterprises. The authors analyze the impact of global economic and scientific-technological changes on economic development, emphasizing the importance of innovation and collaboration among enterprises in the current turbulent market environment. The article examines the historical development of cluster theory, from Alfred Marshall's concept of industrial districts to contemporary studies by Michael Porter and other researchers. It also highlights the role of clusters in stimulating innovation activity, enhancing competitiveness, and improving business process efficiency. Additionally, the authors emphasize the significance of clustering for business internationalization and strengthening regional economies. The advantages of the cluster approach, such as increasing competitiveness, improving the quality of human resources, promoting internationalization, and fostering innovation development, are analyzed. However, the authors also note certain drawbacks and challenges of the cluster approach, including the imperfection and incompleteness of the legislative framework as an effective basis for regulating cluster activities; the need for developing methods of competent cluster management; dependence on regional conditions; the risk of internal competition; and significant coordination costs within clusters. The importance of effective management and state support for ensuring the sustainable development of clusters is emphasized. The authors conclude that clustering is a vital tool for managing industrial enterprises' innovation and investment development, especially in the context of post-war economic recovery in Ukraine with increasing competitiveness, boosting innovation activity, and promoting internationalization.